Crystal-state quad-mode triplet emissions of D-A-A'-D type phosphors with AIEE and visible-light-excited persistent phosphorescence. (April 2021) - Liu, Jianwei; Ma, Zhimin; Li, Zewei; Liu, Yan; Fu, Xiaohua; Jiang, Hong; Ma, Zhiyong; Jia, Xinru
Abstract: Herein, we succeed in finding crystal-state quad-mode triplet emissions through the concept of integration of thermally activated exciton release from T1 * and introducing intramolecular electron coupling. Two new D-A-A′-D type carbazol-nicotinamide isomers (P1 and P2) with the pyridine ring as the core are synthesized. The crowded D-A-A′-D structure makes P1 and P2 in a highly twisted state, which is conducive to lowering the ΔE ST and E TD . Excitingly, P1 and P2 achieve the crystal-state quad-mode triplet emissions, including ultralong room temperature phosphorescence from T1 *, TADP from T1 via thermally activated exciton release (TAER), the original molecular phosphorescence from T1 and TADF from S1 via TAER and reverse intersystem crossing (RISC). Especially, the long-lived emissions of P1 have a rather high quantum yield of 34.3%. The intramolecular electron coupling is observed in the single crystal, verifying the original T1 phosphorescence. The ΔE ST and E TD of the crystals can be calculated experimentally to be 0.19/0.18 eV and 0.19/0.20 eV, respectively, for P1 and P2. And the TAER and RISC process is validated by temperature-dependent experiment. Besides, the P2 crystals manifest fascianting visible-light-excited persistent phosphorescence and P1 shows remarkable AIEE property. To the best of our knowledge, it is the first time to find crystal-state quad-mode triplet emissions at room temperature experimentally. This study is a breakthrough in the development of multi-mode phosphorescence mechanism. Graphical abstract: New D-A-A'-D type structure is utilized to successfully achieve crystal-state quad-mode triplet emissions through the concept of integration of thermally activated exciton release from T1 * and introducing intramolecular electron coupling. Quad-mode triplet emissions involve the original T1 phosphorescence favored by the intramolecular electron coupling, ultralong phosphorescence from T1 *, TADP and TADF released from T1 * due to the low ΔE ST and low E TD . Image 1 Highlights: Two new D-A-A′-D type carbazol-nicotinamide isomers (P1 and P2) with the pyridine ring as the core are synthesized. P1 and P2 achieve the crystal-state quad-mode triplet emissions, including OURTP, TADP, RTP and TADF. The P2 crystals manifest fascianting visible-light-excited persistent phosphorescence and P1 shows remarkable AIEE property.